Pertussis hospitalizations in France (2008–2020): A real-world retrospective analysis of incidence and costs based on the French National Health Data System - Juan C. Vargas-Zambrano; Mickael Arnaud; Ana Antunes; Khalil Karzazi; Johanna Despres; Regis Verdier; Florence Boisnard; Jerome Jund; Cecile Janssen; Didier Pinquier; Denis Macina (Journal of Infection and Public Health, 2025)
Background: Assessing pertussis burden and the impact of the 2013 vaccination schedule update (3 + 1 to 2 + 1 schedule) in France is hindered by non-mandatory reporting. We aimed to estimate the cumulative incidence and hospitalization costs due to pertussis in France between 2008 and 2020. Methods: This observational retrospective cohort study was conducted using claims data from the French National Health Data System (SNDS) (January 2008–December 2020). Cumulative incidence of pertussis-hospitalizations, cumulative incidence ratios, and economic burden were analyzed. Cumulative incidences were estimated as the total pertussis-hospitalizations recorded annually from SNDS with respect to the French population, and expressed per 100,000 inhabitants. Cumulative incidence ratios were estimated using a negative binomial regression adjusted on the cyclical pattern of pertussis disease. Results: Overall, 10,893 patients were hospitalized for pertussis (severe cases: 36.7 % [n = 3997]; Bordetella pertussis disease: 93.3 % [n = 10,158]). Outbreaks were reported in 2009 (n = 1276), 2012–2013 (n = 2762), and 2017–2018 (n = 1727). The age group with the highest proportion of cases was 2–5 months (34.7 %), followed by 0–1 month (18.0 %) and ≥65 years (13.6 %). Cumulative incidence of hospitalization due to Bordetella pertussis disease was similar among infants aged <2 and 2–5 months (cumulative incidence ratio [CIR]=0.96 [0.90–1.02]; comparator: <2 months) and quite low in children aged ≥1 year (CIR≤0.01). Among adults, CIRs increased with age and peaked at ≥65 years (CIR=2.95 [2.57–3.38]; comparator: 18–25 years). CIRs decreased post schedule change (CIR=0.61 [0.43–0.84]; comparator: 3 + 1) and post-implementation of mandatory vaccination policy (CIR=0.68 [0.43–1.08]; comparator: before mandatory vaccination policy) across all age groups. Median overall costs were €3259 (all cases), with higher costs for severe cases and highest costs (€4880) for infants aged <2 months. Conclusion: Results reemphasized the persistent public health challenge of pertussis, especially in infants aged 0–5 months. Findings may guide future vaccination policies in Europe.